CORPORATE SOCIAL RESPONSIBILITY, UKURAN, DAN KINERJA KEUANGAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL MEDIASI - Kawedar, Warsito; Shodiq, Mohammad Fahmi; Handayani, RR. Sri (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2023)
The development of technology and information in the era of globalization has increased public awareness of the role of companies in the environment. Many companies have provided welfare for people's lives. However, the company's activities in running its business will also not be separated from the negative impact on the company's environment. The purpose of this study was determined the effect of corporate social responsibility (CSR) and firm size on earnings management and financial performance and viewed the effectiveness of earnings management as a mediating variable. The population in this study were all manufacturing companies listed on the IDX in 2015-2019, which were 129 companies. Sampling used a purposive sampling and judgment sampling approach, namely the sample had reported complete financial statements for three consecutive periods. Measurement of CSR disclosure refers to the Global Reporting Initiative (GRI) instrument, company size is measured by total assets, financial performance is measured by ROA, and earnings management is measured using the Jones model. Hypothesis testing analysis technique use multiple linear regression analysis. The results of this study indicate that CSR disclosure has a negative and insignificant effect on earnings management and financial performance. However, firm size has a positive and significant effect on earnings management and financial performance. Another finding is that earnings management is able to mediate the effect of firm size on performance.